Bereavement and Commemoration as a building block in Israel’s collective Identity - Tixell, Edith Shamir (Humaniora. Czasopismo Internetowe, 2025)
In October 2023, Hamas carried out a terrorist attack on Israel, resulting in many casualties among the Israeli population, followed by 1300 funerals. This was a horrifying event in the history of the State of Israel, but not the only one, and it appears that cumulative impact of wars, conflicts, and losses over several decades has profoundly shaped Israelis’ collective identity. These events have left a lasting imprint on the nation’s socio-cultural landscape. This article explores the complex relationship between individual experiences of loss and the formation of collective identity in contemporary Israeli society, with a particular focus on the roles of bereavement and commemoration. A semi-structured interview was conducted with 30 participants who had not lost first-degree relatives, they had experienced the deaths of friends, neighbors, military colleagues, or classmates. Additionally, an online survey with open-ended questions was administered to 132 individuals who had lost first-degree kin over the past 50 years. The article traces the evolution of bereavement practices, highlighting the influence of collective memory and trauma on Israeli identity. Drawing on Social Identity Theory (Tajfel & Turner, 1979), the analysis examines how individuals categorize themselves based on shared experiences of bereavement, incorporating concepts of social categorization, comparison, and group membership. Insights from Cultural Trauma Theory (Alexander, 2004) further illuminate the lasting effects of war and loss on Israeli identity. Collective Memory, as examined by Halbwachs (1992), Olick (1998), and Schwartz (1992), emerges as a key factor in fostering resilience and a shared national identity. The conclusion enhances understanding of how historical traumas shape cultural narratives, influencing both individual perceptions and societal ethos. The article discusses the implications for Israeli collective identity and offers recommendations for future research. It provides valuable insights for researchers, policymakers, and others interested in the intricate interplay between bereavement, commemoration, and collective identity in contemporary Israeli society.